Institutional Capital on Trade-Marketing and Environmentally Sustainable Development Policy Making A Research Model Based on Critical Analysis of Nafta - Vargas-Hernández, José (2019)
The aim of this study is to critically analyze the implications in terms of the relationship between cooperation and conflict and institutional capital, as well as their interactions with trade–marketing and environmentally sustainable development policy making under the framework of NAFTA. The critical analysis stems from the question of whether the North American Free Trade Agreement should continue to operate despite the challenges and the institutional capital capacity built by the country members. The methodology is based on literature review aimed to create a relationship between the analytical variables in order to obtain a research construct. This research model is used to critically analyze the implications in terms of cooperation and conflict relationships as institutional capital and their interactions with trade-marketing and environmentally sustainable development policy making. It is concluded that, although the existence of NAFTA is severely questioned, its institutional capital has positive effects on the implications of trade-marketing, however, environmentally sustainable development proves to be conflictive and highly contentious, although some positive effects are developing.